Liga NarodowoDemokratyczna w latach 1957–1960 - Masny, Ignacy (Pamięć i Sprawiedliwość, 2014)
The article presents the history of the Democratic-National League, an opposition organization with a national profile, which operated in the years 1957–1961, in the context of events associated with the Polish national movement after World War II, as well as in the time-frame during which the movement was active – the first years of Gomułka’s government. The author describes the structure of the organization and its programme, trying to find the sources of the ideas which it contained. He also tries to present the links between the Democratic-National League and national activists from outside its structures as well as the Catholic Church. Describing the historical context, the author goes back to the end of World War II, while the main part of the work covers the 1957–1961 period – from the moment of making the decision to set up the organization until its co-founders and key members were sentenced. The main sources for the article were documents from the IPN Archive and interviews with the League members.